Complexos de espécies de Eumorpha Hübner, [1807] (Lepidoptera, Sphingidae) do Estado do Maranhão, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
Eumorpha is a genus of moths that was described by Hübner 1807, and currently has 28 valid species, distributed between temperate and tropical regions of the Americas. 13 species have been recorded for Brazil. The genus is characterized by an extremely robust and smooth-looking body; the posterior edges of the abdominal tergites have relatively long tiered spines in the distal part of the abdomen; eyes are large, with absent eyelashes; the antennas end as a long, thin hook. Another feature that is present in most species is the presence of a dark spot rectangular. Maranhão is a Brazilian State located in the Northeast of the country, its territory composed of three biomes: Cerrado (64%) Amazon (35%) and Caatinga (1%). This work aimed to carry out a study of Eumorpha inventory with a taxonomic and morphological focus of three complexes of species occurring in Maranhão: Eumorpha anchemolus, Eumorpha analis and Eumorpha obliquus. We analyzed 195 specimens belonging to 14 species, eight of which are representatives of the examined complexes, the specimens studied come from 13 municipalities in the State, seven from the Cerrado biome and six from the Amazon biome. This study contributed to the knowledge of the Eumorpha fauna and demonstrated that it is still underestimated throughout the Brazilian territory. With this work the number of species has increased significantly for the State, in addition to bringing the description of a new species, moreover, it showed that the identification carried out only by external “habitus” morphology is not efficient for the analyzed complexes and also showed that the use of genitalia is a good tool in separating species from groups.
Keywords: Biodiversidade; Cerrado; Genitália; Mariposa; Taxonomia; CNPQ::CIÊNCIAS BIOLÓGICAS